The microstructure and tensile properties of new high-manganese low-activation austenitic steel - Litovchenko, Igor Yu; Akkuzin, Sergey A.; Polekhina, Nadezhda A.; Almaeva, Kseniya V.; Linnik, Valeria V.; Kim, Anna V.; Moskvichev, Evgeny N.; Chernov, Vyacheslav M. (Metals)
Using X-ray diffraction, scanning and transmission electron microscopy, the microstructure of a new low-activation chromium-manganese austenitic steel with a high content of manganese and strong carbide-forming elements is studied. Its structure, dislocation character and particle composition are detailed. The processes taking place in the steel under cold-rolling deformation are described. It is shown that the mechanical properties of the new high-manganese steel revealed by testing at 20 and 650 C are comparable with those of well-known analogs or exceed them. Relying on the structural studies, this is attributed to the dispersion and substructural strengthening. Better plastic properties of the steel are associated with the twinning-induced plasticity effect. It is shown that the steel fracture after tension at the test temperatures is mainly ductile dimple transcrystalline with the elements of ductile intercrystalline fracture (at 20 C), while at 650 C the signs of the latter disappear. The low-activation chromium-manganese austenitic steels characterized by increased austenite stability are thought to be promising structural materials for nuclear power engineering.